DESIGN OF LINEAR FEEDBACK CONTROL IN BILINEAR POWER SYSTEM - DAVID UNSULANGI (NIM : 10108019); Pembimbing : Prof. Dr. Roberd Saragih
Many problems in science and engineering have model in the form of bilinear systems such as power systems, nuclear power plants, chemical plants, biomedical systems, and etc. Therefore, many researchers are studying these bilinear systems such as stability, controllability, observability, model reduction, and control optimization from that systems. In this final project, we study how to design a linear state feedback controller for a bilinear power system model that ensures asymptotic stability and satisfy Lyapunov stability criteria. In this case, the power system is an electric power system with two interconnected areas. The purpose of the controller is to stabilize the frequency changes that was one of the output of a power system. The procedures to design the control system begins by modeling the power system in the form of bilinear systems and continued by defining the domain of the state space on the bilinear system. The linear feedback control system can be obtained by solving the Linear Matrix Inequality (LMI). From the numerical simulation, it can be verified that the control system can be used to stabilize the frequency changes of the power system